A multi-stacked hyperporous silicon flake for highly active solar hydrogen production. Issue 67 (7th July 2016) - Jang, Youn Jeong; Ryu, Jaegeon; Hong, Dongki; Park, Soojin; Lee, Jae Sung
Abstract : 3D multi-stacked Si flakes have been successfully fabricated via the selective chemical reduction of natural clay on the strength of an inherently negative catalyst. Their solar-driven hydrogen production performance scored as the highest Si-based photocatalyst for hydrogen evolution with superior stability. Abstract : 3D multi-stacked hyperporous silicon flakes (MHSFs) are prepared via a selective chemical reduction of natural clay minerals bearing MgO negative catalyst layers. The resultant MHSFs are used as a photocatalyst for solar-driven hydrogen evolution and exhibit the highest photocatalytic acitivty (1031 μmol H2 h −1 g −1 Si) coupled with a Pt cocatalyst.